2019
DOI: 10.3389/fpsyt.2019.00010
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of Quality of Life in a Homeless Population

Abstract: Quality of life (QOL) is a key indicator in mental health planning, program evaluation, and evaluation of patient outcomes. Yet few studies have focused on QOL in homeless populations. More specifically, research has yet to identify profiles of homeless individuals based on their QOL using cluster analysis. This study developed a typology of QOL for a sample of 455 homeless individuals recruited from 27 community and public organizations in Quebec (Canada). The typology was developed based on QOL scores, as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 58 publications
4
31
1
1
Order By: Relevance
“…44 Cluster analysis has been used to identify several types of profiles among people with MD-SUD who use diverse health services; for example, patients admitted to hospital for the first time, 45 patients who frequently use in-patient mental health services, 46 people with schizophrenia receiving health services in the community, 47 people with MD-SUD treated in addiction rehabilitation centers, 48 those receiving help from general mental health services, 49 people who use antidepressants 50 and homeless individuals with MD-SUD who use health services. 51 The present study aimed to develop a typology based on the frequency of emergency department visits for MD-SUD among a sample of 320 people in Quebec (Canada).…”
mentioning
confidence: 99%
“…44 Cluster analysis has been used to identify several types of profiles among people with MD-SUD who use diverse health services; for example, patients admitted to hospital for the first time, 45 patients who frequently use in-patient mental health services, 46 people with schizophrenia receiving health services in the community, 47 people with MD-SUD treated in addiction rehabilitation centers, 48 those receiving help from general mental health services, 49 people who use antidepressants 50 and homeless individuals with MD-SUD who use health services. 51 The present study aimed to develop a typology based on the frequency of emergency department visits for MD-SUD among a sample of 320 people in Quebec (Canada).…”
mentioning
confidence: 99%
“…These factors are especially crucial for rehabilitation. One study by Gentilet al (61) found that the quality of life and social integration of homeless individuals were not significantly different between various PHS types. However, there is still a need for more research comparing different types of PHS services to identify their different effects on their users and to identify these users' characteristics.…”
Section: Permanent Housing With Supportmentioning
confidence: 97%
“…Salvia divinorum : 2017 LC-MS/MS analysis of 40 Salvia species for screening their psychoactive constituents of salvinorin A and salvinorin B and genomic characterization [ 847 ]; 2019 review [ 848 ]; review of salvinorin A and some of its analogues [ 849 ].…”
Section: Routine and Improved Analyses Of Abused Substancesmentioning
confidence: 99%